Post Training Evaluation The Alumni Of Reform Leader Academy - Wisber Wiryanto (Iapa Proceedings Conference, 2018)
Bureaucracy in Indonesia faces problems in the areas of human resources apparatus and public services. Therefore, the government made bureaucratic reform efforts. The implementation of bureaucratic reform is supported by efforts to develop the competence of the state of civil apparatus, through education and training. One type of training is the Reform Leader Academy (RLA). RLA has been carried out by the National Institute of Public Administration within 5 (five) years. Therefore, it is necessary to conduct an evaluation study after training the RLA alumni. The formulation of the problem among others: What is the ability of self after RLA training?; What is the relationship between the RLA training material and the competencies needed to carry out the task?; and what are the organizational support for innovative interventions/solutions initiated by alumni? This study is carried out using descriptive methods. The collection data was carried out with collecting data using instruments questionaire. This study focuses on the implementation of reform initiatives by RLA alumni; while the locus is the alumni of the RLA in the west Sumatra provincial government. Collecting data are conducting in September 2018. Furthermore, data are analyzing by qualitative analysis techniques. The results of the post training evaluation of the alumni of the RLA in the West Sumatra Provincial Government showed: (1) The ability of the RLA alumni to vary greatly, remained and decreased. Increased ability in problem analysis, mapping stakeholders and communication to subordinates and colleagues. Permanent ability in communication to stakeholders, motivation, building work teams, conducting innovative strategies and innovative interventions / solutions. Declining abilities in commitment to monitor innovative interventions / solutions due to organizational mutations. (2) The relationship between RLA training materials and the competencies needed to carry out the tasks varies significantly and significantly. There is a significant relationship between the material providing innovative solutions and mapping stakeholders in building effective teams with the competencies needed to carry out the task. And there is a significant relationship between the ability to analyze problems and ensure the successful implementation of innovative solutions with the competencies needed to carry out the task. (3) Organizational support for innovative interventions / solutions initiated by alumni is limited to policy support; while infrastructure support, budget and human resources are not available. Therefore, it is necessary to empower alumni after RLA training through continuous innovation with the support of infrastructure, budget and human resources needed to ensure the continuation of the implementation of the post-training trainee innovations in their work organizations.